PENERAPAN PERATURAN MENTERI ATR/BPN NOMOR 5 TAHUN 2020 DALAM KEGIATAN PELAYANAN HAK TANGGUNGAN TERINTEGRASI SECARA ELEKTRONIK PADA KANTOR PERTANAHAN (Studi Pada Kantor Pertanahan Kabupaten Pesisir Selatan) - Reza, Muhammad; Rosadi, Otong (UNES Law Review, 2023)
Ministerial Regulation ATR/BPN Number 5 of 2020 concerning Electronically Integrated KPR Services has changed conventional mortgage services to an electronic system. With the enactment of Ministerial Regulation ATR/BPN Number 5 of 2020, every land office in Indonesia has provided pawning services electronically. The Pesisir Selatan District Land Office has implemented electronically integrated KPR services. The specification of this research is descriptive analysis. The approach used in this study is a normative juridical approach as the main approach which is supported by an empirical juridical approach. Based on the results of the research, discussion, and analysis it can be concluded as follows: First, the application of Ministerial Regulation ATR/BPN Number 5 of 2020 in Electronically Integrated Pawning Activities at the Land Office of Pesisir Selatan Regency is that when registering Mortgage Rights manually the PPAT must come in person to the BPN office representing the bank takes care of everything up to the issuance of the Mortgage certificate, now the PPAT's task is only to submit APHT through the electronic system. The second obstacle encountered in the Implementation of Permen ATR/BPN Number 5 of 2020 in Electronically Integrated Pawn Service Activities at the Pesisir Selatan District Land Office is more likely to be technical problems related to electronic systems, such as server interruptions and power outages.